A Rare Case of Triple Positive Metachronous Breast Cancer - Hardik S. Chhatrala MD, MPH; John Khuu MD; Lara Zuberi MD (SAGE Publishing, 2019)
Metachronous contralateral breast cancer (MCBC) is defined as contralateral breast cancer (BC) diagnosed more than 1 year after previous BC diagnosis. More BC survivors are at risk of MCBC given improved life expectancy with the availability of advanced cancer care. Estrogen receptor/progesterone receptor negative and HER-2-positive status of first BC are independent risk factors for the development of MCBC. We present a rare case of triple positive (estrogen receptor, progesterone receptor, HER-2 positive) MCBC patient who eventually developed brain metastasis within 15 months despite a near complete pathologic response of primary tumor. This case highlights that even in this era of antiestrogen and anti-HER-2 therapies, triple positive MCBC can have an aggressive clinical course, especially with brain metastasis as the first sign of metastasis.